2013
DOI: 10.1515/bnm-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Biological targeting with nanoparticles: state of the art

Abstract: Nanoparticles are used in medicine to deliver drugs, for imaging, for vaccination and for local heating of tissue (tumor thermotherapy). If malignant tissue shall be addressed, it is of prime importance to direct the nanoparticles to their target. This can be accomplished by making use of physical effects (e.g., the EPR effect: enhanced permeation and retention) or by chemical modification of the nanoparticles to specifically recognize cells or tissues. The efficiency of the targeting can be assessed by in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 111 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…[87] It was also found that nanoparticleso f3 0-150 nm are found in bone marrow,h eart, kidneya nd stomach whereas nanoparticles with as ize of 150-300 nm mainly end up in the liver and in the spleen. [88] Furthermore, the cellular uptake of nanoparticles can be strongly influenced by ap rotein corona, which coversthe particles after their contactw ith biological fluids. [38i, 89] There is av ast literature on nanomedicine and nanomedical approaches (see, for example, [48a, 90] ), but here we will discuss only the applications of calcium phosphate nanoparticles.…”
Section: Biomedical Applications Of Calcium Phosphate Nanoparticlesmentioning
confidence: 99%
“…[87] It was also found that nanoparticleso f3 0-150 nm are found in bone marrow,h eart, kidneya nd stomach whereas nanoparticles with as ize of 150-300 nm mainly end up in the liver and in the spleen. [88] Furthermore, the cellular uptake of nanoparticles can be strongly influenced by ap rotein corona, which coversthe particles after their contactw ith biological fluids. [38i, 89] There is av ast literature on nanomedicine and nanomedical approaches (see, for example, [48a, 90] ), but here we will discuss only the applications of calcium phosphate nanoparticles.…”
Section: Biomedical Applications Of Calcium Phosphate Nanoparticlesmentioning
confidence: 99%
“…6). 9 We identified a clear correlation between the percentage of CD8 + effector T cells and the viral loads: more CD8 + effector T cells in the spleen were correlated with lower viral loads. This demonstrates that an immunization with antigen/adjuvantfunctionalized calcium phosphate nanoparticles is a very efficient method for the induction or reactivation of retrovirusspecific T cell responses, and that they represent a promising approach to improve antiretroviral vaccination.…”
Section: Administration Routes For Vaccinationmentioning
confidence: 72%
“…[2][3][4][5][6][7][8] They can be prepared in various sizes and loaded with different (bio-)molecules, including targeting moieties like antibodies to specifically address different cell types. 9,10 This offers new possibilities because several cargo molecules (e.g. stimulatory molecules and antigen) can be delivered at the same time to the same cell, thereby provoking a fine-tuned immune response.…”
mentioning
confidence: 99%
“…The delivery of therapeutic molecules with the help of nanoparticles is a major goal of nanomedicine [ 3 , 69 , 70 ]. In gene therapy, this is exploited for transfection and gene silencing [ 5 , 6 , 8 ], in immunology, it is used for vaccination and cell stimulation [ 71 73 ], and in tumour therapy, it is used to deliver therapeutic molecules like cytostatics [ 4 , 74 , 75 ]. Typically, a transport of these drugs across the cell membrane is desired, and the functional integrity of the drugs must be assured to preserve the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%